Glacier mass balance in the south-eastern Swiss Alps since 1900 and perspectives for the future - Huss, Matthias; Usselmann, Stephanie; Farinotti, Daniel; Baude, Andreas (ERDKUNDE, 2010)
In this study, we analyzed the 20th century ice volume changes for 20 glaciers in the south-eastern Swiss Alps. Our sample included different glacier geometries, sizes and exposures and allowed us to investigate glacier response to climate change. Using a distributed accumulation and temperature-index melt model, we derived mass balance time series in seasonal resolution from 1900. The model was calibrated using ice volume changes obtained from differentiating digital elevation models based on (i) terrestrial topographic surveys, (ii) the Shuttle Radar Topographic Mission (SRTM), and (iii) aerial photogrammetry. In-situ point measurements of annual mass balance and winter accumulation were available for some glaciers, and long-term discharge records were used for model validation. The rate of mass loss between 1900 to 2008 strongly differed between adjacent glaciers. Whereas large valley glaciers (e.g. Vadrec del Forno) showed average mass balances of up to -0.60 m w.e. a-1, smaller and steeper glaciers (e.g. Vadret da Palü) exhibited slower mass loss in the order of -0.20 m w.e. a-1. Over the last century, the regional ice volume decreased by 47%, with strong differences between individual glaciers (30–75%). Using a combined model for 3D glacier evolution and stream-flow runoff driven by regional climate scenarios, we generated perspectives for the 21st century. We determined a decrease in glacier area of 63% until 2050 and an increase in annual discharge over the next three decades for catchments with high glacierization. By 2100, the model results indicated a shift in the hydrological regime and a 23% decrease in annual runoff attributed to increased evapotranspiration and strongly reduced glacier melt contribution.